The effect of Calendula officinalis versus metronidazole on bacterial vaginosis in women: A double-blind randomized controlled trial - Zahra Pazhohideh; Solmaz Mohammadi; Nosrat Bahrami; Faraz Mojab; Parvin Abedi; Elham Maraghi (Wolters Kluwer Medknow Publications, 2018)
Bacterial vaginosis (BV) is a common disorder among women of reproductive age. This study aimed to compare the effect of a Calendula officinalis extract-based cream and metronidazole on BV among women of reproductive age. In this study, 80 women of reproductive age with BV were randomly assigned to the C. officinalis (n = 40) or metronidazole (n = 40). Diagnosis of BV was confirmed when at least 3 of the 4 Amsel criteria were met (pH> 4.5, whitish grey or thin homogeneous discharge, release of a fishy odor on adding 10% KOH, and detection of clue cells on microscopic examination). For each group, either a methanol extract of C. officinalis or metronidazole vaginal cream (5 g) was used for 1 week intravaginally, and all signs and symptoms were assessed 1 week after treatment completion. Before the intervention, the two groups did not differ significantly with regard to vaginal burning, odor, dysuria, and dyspareunia, but itching was significantly more common in the C. officinalis group than in the metronidazole group (22.5% vs. 2.5%, P = 0.01). One week after the intervention, all women in both groups were free of symptoms, including vaginal itching and burning sensation, odor, dysuria, and dyspareunia. None of the women in either group suffered any side effects from C. officinalis or metronidazole. C. officinalis was effective for the treatment of BV in women of reproductive age, without any side effects. This herb could be recommended for women of reproductive age who uncomfortable with the potential side effects of synthetic drugs.